2020
DOI: 10.1037/pha0000348
|View full text |Cite
|
Sign up to set email alerts
|

Association of SLC1A1 gene polymorphism with obsessive compulsive disorder in a sample from southern India.

Abstract: The study suggests an association of a specific polymorphism (rs3056) of SLC1A1 gene with overall risk of OCD. However, no association is noted with any specific symptoms dimension of OCD or treatment response with serotonin reuptake inhibitors. Brief Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Three patients were partial responders and were excluded from the analysis of treatment response. Responders were those who had >35% reduction in YBOCS (and CGI-I 1 or 2) following an SRI trial; non-responders were those with <25% reduction (and CGI-I >3) even after at least 2 SRI trials (Mataix-Cols et al, 2016; Shukla et al, 2020). All patients were on treatment with SRIs at the time of sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…Three patients were partial responders and were excluded from the analysis of treatment response. Responders were those who had >35% reduction in YBOCS (and CGI-I 1 or 2) following an SRI trial; non-responders were those with <25% reduction (and CGI-I >3) even after at least 2 SRI trials (Mataix-Cols et al, 2016; Shukla et al, 2020). All patients were on treatment with SRIs at the time of sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…Hanna et al (Hanna et al, 2002) showed a strong link between human SLC1A1 gene (Solute Carrier Family 1 Member 1), encoding for the glutamate transporter EAAT3 (Excitatory Amino Acid Transporter 3) in families with OCD. Allelic distribution of several SLC1A1 polymorphisms was associated with OCD diagnosis in family-based association (Arnold et al, 2006;Dickel et al, 2006;Samuels et al, 2011;Shugart et al, 2009;Stewart et al, 2007) and case-control studies (de Salles Andrade et al, 2019;Shukla et al, 2020;Wang et al, 2010;Wendland et al, 2009). In a pharmacogenetic study (Abdolhosseinzadeh et al, 2019b), a significant association between the G allele of both rs2228622 and rs3780413 and fluvoxamine treatment response was observed.…”
Section: Glutamatergic Systemmentioning
confidence: 99%